Relations between morphological and cognitive dimensions of persons with above-average motor abilities - Bala, Gustav (Array, 2009)
Abstract: The set of 33 anthropometric measures and the battery KOG3 to estimate the perceptive, serial and parallel processors were applied on the sample of 217 students of the Faculty of Sport and Physical Education in Novi Sad (Serbia). By means of factor analysis with the oblimin rotation, the following morphological dimensions were obtained and analyzed: 1) longitudinal skeletal dimensionality, 2) transversal skeletal dimensionality, 3) volumen and body mass, 4) subcutaneous fat and 5) head voluminosity. After the transformation of the results from linear model of the relations into the non-monotonous spline function of the forth degree, the results of correlation, canonical correlation and redundancy analyses were subjected to the non-linear model analysis. The obtained results showed that the non-linear model of data analyses indicated more significant relations and explained better the common variance of the two sets of variables